Geopolitical Finance and Investment Dynamics: A Systematic Literature Review on Tax Policy and Economic Stability - Idris , Hariany (Golden Ratio of Taxation Studies, 2026)
This study aims to analyze the dynamic relationship between financial geopolitics, investment dynamics, tax policy, and economic stability through a systematic literature review approach. The research employs a qualitative method using thematic analysis of academic literature published between 2022 and 2026, covering international academic databases such as Scopus, Web of Science, and Google Scholar. The findings identify four main themes: (1) tax policy as an instrument for stimulating investment, (2) geopolitical risk as a barrier to capital mobility, (3) macroeconomic stability as a foundation for sustainable growth, and (4) institutional quality as a moderating factor in the policy–investment relationship. This study contributes to the theoretical understanding of the geopolitics–finance nexus and provides practical implications for policymakers in designing fiscal strategies that are adaptive to global uncertainty.